The Occurrence of Pebbles, Concretions and Conglomerate in Metalliferous Veins - Edward Halse (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
THE occasional occurrence in metalliferous veins of rounded fragments of rock, matrix or ore, lying loose, embedded in clay, or enclosed in some kind of cement, may be attributed to four causes:¬ I. They have been washed in from the surface, or from an upper portion of the vein. II. They are of concretionary origin. III. They have been produced by movements in the country-rock or in the walls of the vein. IV. They have been found in situ, by the upward, downward or lateral flow of water in the vein itself. In this paper the word " conglomerate " is confined to a rock composed of rounded fragments or pebbles cemented together, as distinguished from a " breccia," in which the rock-fragments are angular. I. BOULDERS AND PEBBLES WHICH HAVE BEEN WASHED IN FROM THE SURFACE, OR FROM AN UPPER PORTION OF THE VEIN. In this type it is presupposed that the vein at onetime com¬municated by a fissure or open space with the surface, or with the upper portion from whence the fragments have been washed. One well-authenticated occurrence was described long ago by Fournet. Owing, no doubt, to later dislocations in the lode, pebbles from an old alluvium and sands containing titaniferous iron, as well as fragments of wood, were found in a vein at Huelgoët, in France. "Toutes les parties tendres du filon de Pranal ou ces pédnomènes sont les plus prononcés ont été excavés jusqu'a d'assez grandee profondeurs par l'impétuosité des torrents, qui ont deposé la matière alluviale."1